Improving type 2 diabetes mellitus management in Ministry of Defense Hospitals in the Kingdom of Saudi Arabia 2018–2021 - Noura Al-Nowaiser; Yasser K Alotaibi; Turki J Al Harbi; Ayla M Tourkmani; Maha Moharram (BMJ Open Quality)
Diabetes mellitus is a metabolic disease characterised by elevated levels of blood glucose and is a leading cause of disability and mortality. Uncontrolled type 2 diabetes leads to complications such as retinopathy, nephropathy and neuropathy. Improved treatment of hyperglycaemia is likely to delay the onset and progression of microvascular and neuropathic complications.This article describes the efforts of 18 governmental hospitals in the Kingdom of Saudi Arabia that enrolled in a collaborative improvement project to improve the poor glycaemic control (HbA1c >9% to be less than 15%) of patients with diabetes by the end of 2021 among all the chronic illness clinics in the enrolled military hospitals. Enrolled hospitals were required to implement an evidence-based change package that included the implementation of diabetes clinical practice guidelines with standardised assessment and care planning tools. Furthermore, care delivery was standardised using a standard clinic scope of service that focused on multidisciplinary care teams. Finally, hospitals were required to implement diabetes registries that were used by case managers for poorly controlled patients.The project timetable was from October 2018 to December 2021. Diabetes poor control (HbA1c >9%) showed improved mean difference of 12.7% (34.9% baseline, 22.2% after) with a p value of 0.01. Diabetes optimal testing significantly improved from 41% at the start of the project in the fourth quarter of 2018, reaching 78% by the end of the fourth quarter of 2021. Variation between hospitals showed a significant reduction in the first quarter of 2021.The collaborative multilevel approach of standardising the care based on the best available evidence through policies, guidelines and protocols, patient-focused care and integrated care plan by a multidisciplinary team was associated with noticeable improvement in all key performance indicators of the project.